Pengaruh Kampanye Pencegahan Kejahatan Melalui Spanduk Terhadap Penurunan Angka Kriminalitas : Studi regresi pada curanmor di Polsek Pemali, Polda Bangka Belitung - Laksono, Judit Dwi; Lindiasari, Lindriasari; Halimah, Halimah (Brand Communication, 2025)
Over the past five years, from 2019 to 2023, the Pemali District area in Bangka Regency, Bangka Belitung Islands Province, has consistently experienced an increase in the number of motorcycle theft crimes involving two-wheeled vehicles (R2). The banner media created by the Pemali Police in 2024 contains security messages on how to avoid becoming a victim of motorcycle theft. The aim is to encourage the community to abandon old habits, such as leaving motorcycles unlocked with the key still attached, and instead park their motorcycles in safe places to develop new habits. This research uses a quantitative approach through a questionnaire distributed to 100 respondents. The theories related to this research are the public communication campaign theory, behavior change theory, and crime prevention theory. The research data was processed using simple regression analysis, and the questionnaire was tested for validity and reliability. The responses were then analyzed using SPSS software, which included normality tests, correlation tests, and regression tests. Additionally, heteroscedasticity and autocorrelation tests were conducted. From the questionnaire responses of 100 respondents, hypothesis testing through F-tests, t-tests, and the coefficient of determination showed that crime prevention campaigns through banners affect behavior change in the community and have a 13.5% influence on the reduction of motorcycle thefts in the Pemali Police jurisdiction. The conclusion of this study is that banners influence behavior change in the community and contribute to a 13.5% decrease in motorcycle thefts. It is necessary to combine crime prevention campaigns not only through banners but also through social media platforms such as Facebook, Instagram, X, TikTok, and SnackVideo.